Metafizyka w logice - Wojtysiak, Jacek (Filozofia Nauki, 1999)
The paper contains a survey of existence problems in the folowing calculi of formal logic: calculi of classes, syllogistics, classic predicate calculus, Lesniewski's ontology, quantificational modal calculi, quantificational tense logics, sentential calculi. The particular attention is given to metaphysical (ontological) presuppositions and commitments of logical calculi especially to the problems of empty set, existential axiom (axiom of the non-emptiness of universe of discourse), existential operators (quantifiers and functors), possible worlds, temporal predicates and operators, objects of sentences.